New Strains of Wolbachia Unveiling the Complexity of This Symbiotic Interaction in Solenopsis (Hymenoptera: Formicidae) - Martins, Cintia; Ramalho, Manuela de Oliveira [UNESP]; Rodrigues Silva, Larissa Marin [UNESP]; Souza, Rodrigo Fernando de [UNESP]; Bueno, Odair Correa [UNESP] (Mdpi, 2021)
Bacteria of the genus Wolbachia are widely distributed in arthropods, particularly in ants; nevertheless, it is still little explored with the Multilocus Sequence Typing (MLST) methodology, especially in the genus Solenopsis, which includes species native to South America. Ants from this genus have species distributed in a cosmopolitan way with some of them being native to South America. In Brazil, they are widely spread and preferentially associated with areas of human activity. This study aimed to investigate the diversity of Wolbachia in ants of the genus Solenopsis through the MLST approach and their phylogenetic relationship, including the relationship between mtDNA from the host and the related Wolbachia strain. We also tested the geographic correlation between the strains to infer transmission and distributional patterns. Fifteen new strains and eleven previously unknown alleles were obtained by sequencing and analyzing the five genes that make up the MLST. The phylogenetic relationship between the strains showed a polyphyletic pattern, indicative of the complexity of the evolutionary history of these bacteria in the analyzed species. We detected the correlation of host's mitochondrial DNA with Wolbachia diversity which imply that related strains exist in related hosts, strongly suggesting the occurrence of vertical transfer. We found no specificity of the Wolbachia strain for a given geographic region that could indicate either that there is no horizontal transfer of the strain from the environment for the host or that the human action could be shuffling the distribution of the Solenopsis ants and the endosymbiont Wolbachia, as well. Our study highlights the complexity and novelty of Wolbachia diversity with this specific group of ants and the need for further studies that focus on understanding of this intricate relationship.
Keywords: Multilocus Sequence Typing; endosymbiont; South America; ants